903 Improving Documentation of Tourniquet Use in a Trauma Unit in Line with New BOAST Guidelines. (19th August 2022) - Fitzpatrick, N; Arneill, M; Wilson, L
Abstract: Aim: Local tissue damage is a significant potential consequence of intraoperative pneumatic tourniquet use, via pressure-related damage or chemical injury. The British Orthopaedic Association released a guideline relating to the safe intraoperative tourniquet use in October 2021, dictating standards for documentation in operative records. Initial audit suggested that only 15% of the required information was documented. With updated operative record paperwork and electronic templates, we aimed to improve adherence to updated BOAST guidance. Method: Following analysis of 14 days' worth of trauma operation records, results of local documentation of tourniquet use were presented at a departmental audit meeting. With departmental permission, changes were made to the operation notes template, to include tickboxes relating to the use of tourniquets, skin condition pre/post-operatively, method of isolation, method of exsanguination, and the pressure of tourniquet and duration of use in line with new guidelines. Additionally, a new, time-efficient template was designed for those using electronic records. Results were re-audited over a 14-day period following dissemination of the relevant templates. Results: Initial results suggested that only 15% of required data surrounding tourniquet use was being documented, with none recording information relating to skin condition pre/post-operatively, method of isolation or exsanguination. Following aforementioned interventions led to an improvement in documentation from 15% compliance to 64% compliance. Conclusions: Further efforts are required in order to further improve documentation of tourniquet use, particularly when in electronic format, initial re-audit results are encouraging for improved adherence to new BOAST guidance in a local trauma unit.